2020
DOI: 10.1523/jneurosci.1156-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Activation Accounts for the Cytoprotective Effects of PERK Activation on Oligodendrocytes during EAE

Abstract: Previous studies demonstrate that activation of pancreatic ER kinase (PERK) protects oligodendrocytes against inflammation in the experimental autoimmune encephalomyelitis (EAE) model of multiple sclerosis (MS). Interestingly, data indicate that the cytoprotective effects of PERK activation on oligodendrocytes during EAE are not mediated by activating transcription factor 4 (ATF4) but are accompanied by activation of nuclear factor jB (NF-jB). NF-jB plays a critical role in MS and EAE; however, the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Since ROS activates NF-κB signaling, which modulates gene expression in diverse cellular processes such as innate immune response ( 29 , 30 ), we next determined if NF-κB plays were required for the expression of inflammatory transcription factors in our EAE model. To do this, we co-stained the active form of NF-κB (pNF-κB) with NeuN or CD11b ( Figure 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…Since ROS activates NF-κB signaling, which modulates gene expression in diverse cellular processes such as innate immune response ( 29 , 30 ), we next determined if NF-κB plays were required for the expression of inflammatory transcription factors in our EAE model. To do this, we co-stained the active form of NF-κB (pNF-κB) with NeuN or CD11b ( Figure 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…The Hg 0 removal efficiency decreases with the increase of the relative humidity. It is mainly due to the water molecules attached to the surface of AC leading part of the micropores clogged, which reduced the surface area of Hg 0 adsorption and hindered the contact of Hg 0 with the active sites . As a result, both the physisorption and chemisorption were weakened.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that p65 aids in survival of oligodendrocytes in vitro [ 131 , 132 , 133 ]. However, constitutively active IKKβ in oligodendrocytes of mice had little effect on the survival and functions of oligodendrocytes under normal conditions [ 134 ]. By contrast, during EAE, these mice had reduced demyelination, oligodendrocyte death, and axon degeneration, resulting in overall decreased disease severity [ 134 ].…”
Section: Relbmentioning
confidence: 99%
“…However, constitutively active IKKβ in oligodendrocytes of mice had little effect on the survival and functions of oligodendrocytes under normal conditions [ 134 ]. By contrast, during EAE, these mice had reduced demyelination, oligodendrocyte death, and axon degeneration, resulting in overall decreased disease severity [ 134 ]. This phenotype was attributed to the activation of p65 and increased p65-dependent oligodendrocyte survival [ 133 , 134 ].…”
Section: Relbmentioning
confidence: 99%
See 1 more Smart Citation